(untitled) (Bangladesh Pharmaceutical Journal, 2020)
Sansevieria trifasciata is a common perennial ornamental plant which freely grows and widely found in homes, parks, and woodlands. Traditionally, this plant has been used against acne, allergy, helminths and fungal infections. In the present study, the ethanolic extract of leaves of Sansevieria trifasciata (STET) has been used to study the phytoconstituents and several bioactivities. In vitro antioxidant activity of STET has been determined by DPPH scavenging assay and measuring the total tannins and phenolic contents. Anti-inflammatory activity has been evaluated by hypotonic solution and heat induced hemolysis. Moreover, cytotoxic and analgesic activities have also been evaluated by brine shrimp lethality assay and acetic acid induced writhing inhibition method, respectively. STET confirmed the presence of reducing sugar, combined reducing sugar, tannins, flavonoids, glycosides, proteins and steroids. In DPPH scavenging assay, STET revealed the IC50 value 2.19 μg/ml whereas the standard showed 1.39 μg/ml. In addition, the total tannins and total phenolic contents were found to be 10.78 mg and 31.99 mg GAE/g of dried plant extract, respectively. In hypotonic solution induced hemolysis test, the plant extract exhibited 39.27, 37.04 and 33.19 % inhibition at 0.5, 1.0 and 2.0 mg/ml concentration where the reference standard displayed 30.57 % inhibition. In heat-induced hemolysis, the STET also displayed 34.25 % inhibition of hemolysis at 1 mg/ml. Furthermore, in analgesic and cytotoxic activity tests, STET showed potential activities in a dose dependent manner. The results of the present studies suggest that STET has antioxidant, anti-inflammatory, cytotoxic and analgesic activities. Bangladesh Pharmaceutical Journal 23(2): 195-200, 2020